2016
DOI: 10.1002/elan.201501056
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunoassay for Cytomegalovirus Antigen Detection with Multiple Signal Amplification Using HRP and Pt‐Pd Nanoparticles Functionalized Single‐walled Carbon Nanohorns

Abstract: Cytomegalovirus is typically associated with immunocompromised hosts, pregnant women and transplant patients, who require a timely diagnosis. In this work, a sensitive and highly specific electrochemical amplification immunosensor was established for detecting Cytomegalovirus pp65 antigen based on Pt‐PdNPs@SWCNHs with horseradish peroxidase (HRP) as a signal enhancer and thionine as a signal probe. First, Pt nanoparticle (PtNP) and Pd nanoparticle (PdNP) functionalized single‐walled carbon nanohorn (SWCNH) nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Owing to the unique structure of the electronic bands of graphene, it shows extraordinary thermal, electrical, and mechanical properties. [114][115][116][117] In recent years, other carbon allotropes such as nanohorns, 118 nanodiamonds, 119,120 and nanoparticles 121,122 have also been introduced into sensing and imaging technologies due to their superior fluorescence, impedance, and energy transfer capabilities. These qualities make carbon allotrope-based nanomaterials ideal for incorporation into biosensing and bioimaging platforms.…”
Section: Carbon Allotrope-based Nanomaterials In Virus Sensing and Tr...mentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the unique structure of the electronic bands of graphene, it shows extraordinary thermal, electrical, and mechanical properties. [114][115][116][117] In recent years, other carbon allotropes such as nanohorns, 118 nanodiamonds, 119,120 and nanoparticles 121,122 have also been introduced into sensing and imaging technologies due to their superior fluorescence, impedance, and energy transfer capabilities. These qualities make carbon allotrope-based nanomaterials ideal for incorporation into biosensing and bioimaging platforms.…”
Section: Carbon Allotrope-based Nanomaterials In Virus Sensing and Tr...mentioning
confidence: 99%
“…Such nanocomposites show promising durability with only 5.8% signal loss in 15 days for horseradish peroxidase-based immunosensing of cytomegalovirus which is often responsible for diseases such as pneumonia and mononucleosis. 118 Crystal defects such as vacancies as well as doping give rise to unique properties at the nanoscale. 177 Fig.…”
Section: Mostmentioning
confidence: 99%
See 1 more Smart Citation
“…Until 2010, not many electrochemical immunosensors based on CNHs were reported. During the last ten years, they have been employed both as electrode materials [76][77][78][79] and as electrocatalytic tracers/nanocarriers [40,80,81].…”
Section: Carbon-based Nanomaterials (Nms)mentioning
confidence: 99%
“…Pires et al [20] proposed a method to detect glycoprotein B of HCMV (gB-HCMV) in urine samples using magnetic particle-based enzyme immunoassay (mpEIA), with a detection limit of 30 pg/ml. Huang et al [21] reported an electrochemical amplification immunosensor for detecting the UL83antigen of cytomegalovirus using horseradish peroxidase attached to single-walled carbon nanohorns decorated by Pt and Pd nanoparticles with a detection limit of 30 pg/ml.…”
Section: Introductionmentioning
confidence: 99%